Diurnal Response of Photosystem I to Fluctuating Light Is Affected by Stomatal Conductance - Ting-Yu Li (MDPI AG, 2021)
Upon a sudden transition from low to high light, electrons transported from photosystem II (PSII) to PSI should be rapidly consumed by downstream sinks to avoid the over-reduction of PSI. However, the over-reduction of PSI under fluctuating light might be accelerated if primary metabolism is restricted by low stomatal conductance. To test this hypothesis, we measured the effect of diurnal changes in stomatal conductance on photosynthetic regulation under fluctuating light in tomato (Solanum lycopersicum) and common mulberry (Morus alba). Under conditions of high stomatal conductance, we observed PSI over-reduction within the first 10 s after transition from low to high light. Lower stomatal conductance limited the activity of the Calvin–Benson–Bassham cycle and aggravated PSI over-reduction within 10 s after the light transition. We also observed PSI over-reduction after transition from low to high light for 30 s at the low stomatal conductance typical of the late afternoon, indicating that low stomatal conductance extends the period of PSI over-reduction under fluctuating light. Therefore, diurnal changes in stomatal conductance significantly affect the PSI redox state under fluctuating light. Moreover, our analysis revealed an unexpected inhibition of cyclic electron flow by the severe over-reduction of PSI seen at low stomatal conductance. In conclusion, stomatal conductance can have a large effect on thylakoid reactions under fluctuating light.